A role of the norepinephrine system or effort in the interplay of different facets of inhibitory control. (10th February 2022) - Yu, Shijing; Ghin, Filippo; Mückschel, Moritz; Ziemssen, Tjalf; Stock, Ann-Kathrin; Beste, Christian
Abstract: Inhibitory control has multiple facets, and one possible distinction can be made between 'inhibition of interferences' and the 'inhibition of actions'. Both facets of inhibitory control show an interdependency. Even though some neurophysiological processes underlying this interdependency have been examined, the role of neuro-modulatory processes in their interplay are not understood. In the current study, we examine the role of the norepinephrine (NE) system in these processes. We did so by combining a Go/Nogo and Simon task. We recorded the EEG and pupil diameter data as an indirect index of NE system activity during the task. EEG theta band activity data and pupil diameter data were then integrated after conducting a temporal signal decomposition of the EEG data. We show that particularly theta band activity coding stimulus-response translation processes associated with middle frontal cortices, but not stimulus-driven processes are modulated by the interplay between the 'inhibition of interferences' and the 'inhibition of actions'. Modulations in stimulus-response translation processes were systematically correlated with pupil-diameter responses. The pattern of correlations suggests that phasic NE system activity particularly modulates stimulus-response mapping processes during conflict monitoring in incongruent Nogo trials, which may explain behavioral performance effects. Phasic NE system activity reflects essential modulators of the interplay between the 'inhibition of interferences' and the 'inhibition of actions'. Highlights: 'Inhibition of interferences' facilitates the process of 'inhibition of actions'. The interplay between them is associated with frontal theta activities. Norepinephrine system or effort modulates this interplay. NE modulation was particularly strong in stimulus-response translation processes.